Numerical-experimental comparison of radial fans applied in pneumatic transport of agricultural fertilizer spreaders - Fogal, Marcelo L. de F. [UNESP]; Micheli, Gustavo B. [UNESP]; Scalon, Vicente L. [UNESP]; Padilha, Alcides [UNESP] (Univ Federal Campina Grande, 2021)
This study presents a numerical and experimental comparison of two different types of radial fans used in an agricultural fertilizer spreader at a rotation of 4000 rpm. The numerical analysis was validated through experiments conducted on a test bench using a hot-wire anemometer for velocity measurements and a Pitot tube for pressure readings. A simulation of the agricultural fertilizer spreader was carried out after the experimental validation of the mathematical models of the radial fans on the test bench to evaluate the air distribution behavior along the application nozzles, which was compared to the experimental results. A turbulent mean-field was obtained using the Reynolds Averaged Navier Stokes (RANS) and the k-Epsilon turbulence model was used for two equations. The computational fluid dynamics software CFX 18.1 was used to solve the transport equations. Unstructured tetrahedral meshes generated by the ICEM CFD 18.1 software were used in all models. The applied method is adequate and able to reproduce the fluid-dynamic behavior of airflow in pneumatic systems of agricultural fertilizer spreaders, avoiding the need for prototypes.
Keywords: turbulence model; computational fluid dynamics; CFX; hot-wire anemometer; Pitot tube